The Practice of Retransplantation for Recurrent Alcohol-associated Liver Disease in the United States Is Uncommon With Acceptable Outcomes. Issue 3 (March 2022) - Cotter, Thomas G.; Odenwald, Matthew A.; Lieber, Sarah R.; Rich, Nicole E.; Im, Gene; Charlton, Michael; Singal, Amit G.; Mitchell, Mack C.
Abstract : Background: Alcohol-associated liver disease (ALD) is the leading indication for liver transplantation (LT) in the United States. Alcohol use disorder relapse can lead to graft failure and the need for liver retransplantation (re-LT). Despite the rising incidence of LT for ALD, the practice of re-LT for recurrent ALD is not well understood. We aimed to define the practice of re-LT for recurrent ALD during the last 20 y. Methods: Using the US national transplant registry, adults who underwent re-LT for recurrent ALD were compared with LT recipients who died from recurrent ALD and propensity score–matched re-LT recipients with non-ALD indications. All groups had at least 1-y survival of their primary graft. Kaplan-Meier analysis was used to calculate 1- and 5-y survivals. Results: Between 2000 and 2020, 74 re-LTs were performed for recurrent ALD (1.0% of all re-LTs). There was an increase in recurrent ALD re-LT practice from 2017 to 2020 versus 2014 to 2016 (20 versus 2). At the time of re-LT, patients with recurrent ALD had a significant decrease in body mass index (median 25.1 versus 28.8 kg/m 2 ; P  < 0.001) versus the index LT. Patient and graft survivals were similar between patients who underwent re-LT for ALD and non-ALD (56.4% versus 56.9% 5-y graft survival, P  = 0.96; 62.8% versus 59.0% 5-y patient survival, P  = 0.58). Conclusions: The practice of re-LT for recurrent ALD is uncommon in the United States. Graft and patient survivals seem to be acceptable and support the occasional practice of re-LT for recurrent ALD should the patient be deemed an appropriate candidate.